EDUCATION OF ELEMENTARY SCHOOL STUDENTS IN THE SPIRIT OF PATRIOTISM THE CURRENT STATE OF USING UZBEK FOLK TALES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article discusses the current state of using Uzbek folk tales to educate elementary school students in the spirit of patriotism.